Bactericidal antibody persistence 2 years after immunization with 2 investigational serogroup B meningococcal vaccines at 6, 8 and 12 months and immunogenicity of preschool booster doses: A follow-on study to a randomized clinical trial - Snape, MD; Philip, J; John, T; Robinson, H; Kelly, S; Gossger, N; Yu, L; Kittel, C; Toneatto, D; Dull, P; Pollard, A (2013)
Background: In a previous study, 60 infants receiving an investigational serogroup B meningococcal vaccine containing recombinant meningococcal proteins alone (rMenB) or combined with an outer membrane vesicle from Neisseria meningitidis (4CMenB) at 6, 8 and 12 months of age produced serum bactericidal antibodies (SBAs) against meningococcal strains expressing vaccine antigens. We studied persistence of this response and the response to a booster dose of vaccine. Methods: In this extension study, SBA titers were evaluated before and after a booster dose of rMenB or 4CMenB at 40 months of age. MenB vaccine naïve age-matched children served as a control group. Results: Before the booster doses, the proportions of 4CMenB recipients with SBA titers ≥1:4 were 36% (n = 14, 95% confidence interval: 13-65%) for strain 44/76-SL, 100% (77-100%) for 5/99, 14% (2-43%) for NZ98/254 and 79% (49-95%) for M10713. These percentages were 14% to 29% for rMenB recipients (n = 14), except for 5/99 (93%, 66-100%). For controls (n = 40), these proportions were ≤3% for all strains except M10713 (53%, 36-68%). One month after the boosters, ≥93% of 4CMenB recipients had SBA titers ≥1:4 for all 4 strains. For controls receiving their first dose of 4CMenB, 23% (11-39%) had SBA titers ≥1:4 for NZ98/254, compared with 62% to 87% for the remaining strains. Conclusions: Bactericidal antibodies wane after infant immunization with rMenB or 4CMenB, but there is an anamnestic response to a booster dose. Booster doses of 4CMenB may be required to maintain immune protection through childhood and adolescence. Copyright © 2013 by Lippincott Williams and Wilkins.